Road Map or Mosaic: Relationships among Learning, Context and Professional Practice - Barbara J Daley (Adult Education Research Conference, 2000)
This qualitative interpretivist study analyzed the interrelationships among professional practice, the knowledge gained in continuing professional education programs, and the context of employment. Social workers, lawyers, adult educators and nurses participated in this study.